Slurry and method of screening thereof, and method of grinding

CN112930585BActive Publication Date: 2026-10-27RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201880097068.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-07-26
Filing Date
2018-09-25
Publication Date
2026-10-27
Estimated Expiration
2038-09-25

AI Technical Summary

Benefits of technology

[0020]根据本发明,能够提供一种可提高绝缘材料的研磨速度的浆料。并且,根据本发明,能够提供一种浆料的筛选方法,所述方法能够选定可提高绝缘材料的研磨速度的浆料。此外,根据本发明,能够提供一种可提高绝缘材料的研磨速度的研磨方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002957126710000231
    Figure BDA0002957126710000231
Patent Text Reader

Abstract

The slurry of the present application is a slurry containing abrasive grains and a liquid medium, wherein the abrasive grains contain at least one metal compound selected from the group consisting of metal oxides and metal hydroxides, the metal compound containing a metal which can have a plurality of valence numbers, and the slurry gives a value of 0.13 or more in the proportion of the smallest valence number among the plurality of valence numbers of the metal in X-ray photoelectron spectroscopy when the abrasive grains are brought into contact with a surface to be polished by bringing the slurry into contact with the surface to be polished.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a slurry, a screening method thereon, and a grinding method. Background Technology

[0002] In recent years, the importance of processing technologies for high-density and miniaturization in semiconductor device manufacturing processes has been increasing. CMP (Chemical Mechanical Polishing), as one such processing technology, has become essential for shallow trench isolation (STI) formation, planarization of pre-metal or interlayer insulating materials, and the formation of plugs or embedded metal wiring in semiconductor device manufacturing processes.

[0003] As the most commonly used polishing slurry, examples include silica-based polishing slurries that contain silica (silica) particles such as fumed silica and colloidal silica as abrasives. Silica-based polishing slurries are characterized by their high versatility; by appropriately selecting the abrasive content, pH, and additives, they can polish a wide variety of materials, including both insulating and conductive materials.

[0004] On the other hand, the demand for polishing slurries containing cerium compound particles as abrasives is also increasing, as polishing slurries are mainly used for insulating materials such as silicon oxide. For example, cerium oxide-based polishing slurries containing cerium oxide particles as abrasives can polish silicon oxide at high speeds even when the abrasive content is lower than that of silicon dioxide-based polishing slurries (see, for example, Patent Documents 1 and 2 below).

[0005] Previous technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 10-106994

[0008] Patent Document 2: Japanese Patent Application Publication No. 08-022970 Summary of the Invention

[0009] The technical problem to be solved by the invention

[0010] In recent years, 3D-NAND devices with longitudinally stacked trenches have emerged. In this technology, the step difference of the insulating material during trench formation is several times higher than that of conventional planar type. Consequently, in order to maintain the yield rate of device manufacturing, it is necessary to eliminate the high step difference mentioned above as soon as possible in processes such as CMP, which requires increasing the polishing speed of the insulating material.

[0011] The present invention aims to solve the above-mentioned problems, and its object is to provide a slurry that can improve the grinding speed of insulating materials. Furthermore, the present invention aims to provide a slurry screening method that can select a slurry that can improve the grinding speed of insulating materials. In addition, the present invention aims to provide a grinding method that can improve the grinding speed of insulating materials.

[0012] means for solving technical problems

[0013] One aspect of the present invention relates to a slurry containing abrasive particles and a liquid medium, wherein the abrasive particles comprise at least one metal compound selected from the group consisting of metal oxides and metal hydroxides, the metal compound comprising a metal that may have multiple valences, and when the abrasive particles are brought into contact with the surface being ground by contacting the slurry with the surface being ground, the slurry gives a value of 0.13 or more in X-ray photoelectron spectroscopy as the proportion of the smallest valence of the metal among the multiple valences.

[0014] This slurry can increase the grinding speed of insulating materials and enable the grinding of insulating materials at high speeds.

[0015] Another aspect of the present invention relates to a slurry screening method comprising: a step of contacting the abrasive particles with the surface being ground by contacting the slurry containing abrasive particles and a liquid medium with the surface being ground; and a measurement step in which, while the abrasive particles are in contact with the surface being ground, the valence of a metal contained in the abrasive particles is determined by X-ray photoelectron spectroscopy, wherein the abrasive particles contain at least one metal compound selected from the group consisting of metal oxides and metal hydroxides, the metal compound containing a metal that may have multiple valences, and in the measurement step, the proportion of the smallest valence among the multiple valences of the metal is obtained.

[0016] Based on this slurry screening method, it is possible to select slurries that can improve the grinding speed of insulating materials.

[0017] Another aspect of the present invention relates to a grinding method comprising a step of grinding the surface to be ground using a slurry having a value of 0.13 or more, given by the proportion of the valence obtained in the determination step of the above-described slurry screening method.

[0018] This grinding method can increase the grinding speed of insulating materials and enable the grinding of insulating materials at high speeds.

[0019] Invention Effects

[0020] According to the present invention, a slurry capable of increasing the grinding speed of insulating materials can be provided. Furthermore, according to the present invention, a method for screening the slurry can be provided, the method being capable of selecting a slurry capable of increasing the grinding speed of insulating materials. Additionally, according to the present invention, a grinding method capable of increasing the grinding speed of insulating materials can be provided.

[0021] According to the present invention, a paste can be provided for use in grinding a surface containing an insulating material. According to the present invention, a paste can be provided for use in a planarization process of a substrate surface as part of a semiconductor device manufacturing technology. According to the present invention, a paste can be provided for use in a planarization process of STI insulating materials, pre-metal insulating materials, or interlayer insulating materials. Detailed Implementation

[0022] The embodiments of the present invention will now be described in detail. However, the present invention is not limited to the following embodiments.

[0023] <Definition>

[0024] In this specification, the numerical range indicated by "~" represents the range of minimum and maximum values, including the values ​​before and after "~". Within the numerical ranges described in stages in this specification, the upper or lower limit of a certain stage's numerical range can be arbitrarily combined with the upper or lower limit of another stage's numerical range. The upper or lower limit of the numerical range described in this specification can also be replaced with the values ​​shown in the embodiments. The term "A or B" can include either A or B, or both. Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. In this specification, when multiple substances equivalent to each component are present in the composition, unless otherwise specified, the content of each component in the composition refers to the total amount of the multiple substances present in the composition. The term "process" not only refers to an independent process, but is also included in this terminology as long as the intended function of the process can be achieved, even when it is difficult to clearly distinguish it from other processes.

[0025] As described later, the slurry involved in this embodiment contains abrasive grains. Abrasive grains are also called "abrasive particles," but are referred to as "abrasive grains" in this specification. Abrasive grains are generally considered to be solid particles that remove the object to be removed during grinding through the mechanical action (physical action) and chemical action of the abrasive grains (mainly the surface of the abrasive grains), but are not limited to this.

[0026] In this specification, the term "polishing liquid" (or "abrasive") is defined as the composition that comes into contact with the surface being polished during polishing. The term "polishing liquid" itself does not limit the composition of the polishing liquid.

[0027] The weight-average molecular weight in this specification can be determined, for example, using a calibration curve of standard polystyrene and by gel permeation chromatography (GPC) under the following conditions.

[0028] Equipment used: Hitachi L-6000 model [manufactured by Hitachi, Ltd.]

[0029] Tube Columns: Gel pack GL-R420 + Gel pack GL-R430 + Gel pack GL-R440 [Manufactured by Hitachi Chemical Co., Ltd., trade name, 3 columns in total]

[0030] Eluent: Tetrahydrofuran

[0031] Measurement temperature: 40℃

[0032] Flow rate: 1.75 mL / min

[0033] Detector: L-3300RI [Manufactured by Hitachi, Ltd.]

[0034] <Pulp>

[0035] The slurry described in this embodiment contains abrasive particles and a liquid medium as essential components. The slurry described in this embodiment can, for example, be used as a polishing fluid (CMP polishing fluid).

[0036] The abrasive grains comprise at least one metal compound selected from the group consisting of metal oxides and metal hydroxides, and the metal compound comprises a metal that may have multiple valences (atomic valences). Furthermore, when the abrasive grains are brought into contact with the surface being ground by contacting the slurry with the surface being ground, the slurry according to this embodiment exhibits a proportion of the smallest valence among the multiple valences of the aforementioned metal that is 0.13 or higher in X-ray photoelectron spectroscopy (XPS).

[0037] By using the slurry according to this embodiment, the grinding speed of insulating materials (e.g., silicon oxide) can be increased. The reasons for such an increase in the grinding speed of insulating materials are given below, for example, using silicon oxide. However, the reasons are not limited to those described below.

[0038] That is, during the grinding of silicon oxide, the following stages occur: In the first stage, metal atoms in the abrasive grains bond with silicon atoms in the silicon oxide via oxygen atoms (for example, in the case of cerium, a Ce-O-Si bond is formed); and in the second stage, while maintaining the metal-oxygen-silicon atom bonds, the bonds between silicon atoms and other oxygen atoms in the ground surface are broken, and silicon atoms are removed from the ground surface. Furthermore, after the abrasive grains come into contact with the silicon oxide, the higher the proportion of the lowest valence among the metal valences in the abrasive grains, the easier it is to perform the first stage, thus facilitating the overall grinding of the silicon oxide. From this perspective, when the proportion of the lowest valence among the multiple valences of the metal contained in the abrasive grains is above the aforementioned predetermined value, the first stage is easily performed, thus facilitating the overall grinding of the silicon oxide. Through the above, the grinding speed of silicon oxide is increased.

[0039] (Abrasive grains)

[0040] The abrasive grains of the slurry involved in this embodiment comprise at least one metal compound selected from the group consisting of metal oxides and metal hydroxides, and the metal compound comprises a metal that may have multiple valences (hereinafter referred to as "metal M"). That is, the abrasive grains comprise at least one selected from the group consisting of oxides containing metal M and hydroxides containing metal M.

[0041] From the viewpoint of further improving the grinding speed of insulating materials, metal M is preferably composed of at least one element selected from the group consisting of silicon (Si), vanadium (V), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), silver (Ag), indium (In), tin (Sn), rare earth elements (rare earth metal elements), tungsten (W), and bismuth (Bi). From the viewpoint of further improving the grinding speed of insulating materials, metal M is preferably composed of at least one rare earth element selected from the group consisting of scandium (Sc) and lanthanides. From the viewpoint of further improving the grinding speed of insulating materials, metal M is preferably composed of at least one lanthanide element selected from the group consisting of cerium (Ce), praseodymium (Pr), europium (Eu), terbium (Tb), and ytterbium (Yb). From the viewpoint of further improving the grinding speed of insulating materials, metal M is preferably composed of a rare earth element, more preferably a lanthanide element, and even more preferably cerium.

[0042] From the viewpoint of further improving the grinding speed of insulating materials, the abrasive grains are preferably at least one selected from the group consisting of cerium oxides (oxides containing cerium) and cerium hydroxides (hydroxides containing cerium).

[0043] Examples of cerium oxides include oxides containing tetravalent cerium (cerium(IV), cerium dioxide, CeO2) and oxides containing trivalent cerium (cerium(III), Ce2O3). In the case of cerium oxides containing both trivalent and tetravalent cerium, the smallest valence among the various valences of metal M is trivalent.

[0044] Cerium oxides can be produced, for example, by oxidizing cerium salts such as carbonates, nitrates, sulfates, and oxalates. Examples of oxidation methods include: calcination, where the cerium salt is calcined at a temperature of approximately 600–900°C; and chemical oxidation, where the cerium salt is oxidized using an oxidizing agent such as hydrogen peroxide.

[0045] Cerium hydroxides, for example, contain cerium ions and at least one hydroxide ion (OH-). - Compounds containing cerium hydroxides. Cerium hydroxides may also contain anions other than hydroxide ions (e.g., nitrate ions, NO3-). - and sulfate ions SO4 2- For example, cerium hydroxides may also contain anions bonded to cerium ions (e.g., nitrate ions, NO3-). - and sulfate ions SO4 2- ).

[0046] Cerium hydroxides can be produced by reacting a cerium salt with an alkaline source (alkali). Cerium hydroxides can also be produced by mixing a cerium salt with an alkaline solution (e.g., an alkaline aqueous solution). Cerium hydroxides can be obtained by mixing a cerium salt solution (e.g., an aqueous solution of a cerium salt) with an alkaline solution. Examples of cerium salts include Ce(NO3)4, Ce(SO4)2, Ce(NH4)2(NO3)6, and Ce(NH4)4(SO4)4.

[0047] It is believed that the formation of Ce(OH) compounds depends on factors such as the manufacturing conditions of cerium hydroxide. a X b (In the formula, a + b × c = 4) particles (in addition, these particles are also cerium hydroxide), the Ce(OH) a X b Composed of cerium ions and 1 to 3 hydroxide ions (OH-) - ) and 1 to 3 anions (X c- It is composed of Ce(OH). Furthermore, it is believed that... a X b In the middle, electron-withdrawing anions (X c- This increases the reactivity of hydroxide ions due to the action of Ce(OH)₂, and with the action of Ce(OH)₂ a X b The increased presence of X leads to a higher grinding speed. As an anion (X... c- For example, NO3 can be listed. - and SO42- It is believed that particles containing cerium hydroxide may contain not only Ce(OH) a X b It can also contain Ce(OH)4, CeO2, etc.

[0048] Regarding particles containing cerium hydroxide, they contain Ce(OH). a X b The following method can be used to confirm this: after thoroughly washing the particles with pure water, the equivalent of anions (X-rays) can be detected using the FT-IR ATR method (Fourier transform infrared spectrophotometer attenuated total reflection). c- The peak of the anion (X-ray photoelectron spectroscopy) can also be used to confirm the anion (X). c- The existence of ).

[0049] The average particle size (average secondary particle size) of the abrasive particles in the slurry is preferably within the following range. From the viewpoint of further increasing the grinding speed of the insulating material, the lower limit of the average particle size of the abrasive particles is preferably 16 nm or more, more preferably 20 nm or more, further preferably 30 nm or more, particularly preferably 40 nm or more, extremely preferably 50 nm or more, very preferably 100 nm or more, even more preferably 120 nm or more, and even more preferably 140 nm or more. From the viewpoint of improving the dispersibility of the abrasive particles and easily suppressing damage to the ground surface, the upper limit of the average particle size of the abrasive particles is preferably 1050 nm or less, more preferably 1000 nm or less, further preferably 800 nm or less, particularly preferably 600 nm or less, extremely preferably 500 nm or less, very preferably 400 nm or less, even more preferably 300 nm or less, even more preferably 200 nm or less, particularly preferably 160 nm or less, and extremely preferably 155 nm or less. From the aforementioned viewpoint, the average particle size of the abrasive particles is more preferably 16 to 1050 nm.

[0050] The average particle size can be measured, for example, using a light diffraction scattering particle size analyzer (e.g., Beckman Coulter, Inc., trade name: N5, or Microtrac BEL, Inc., trade name: MicrotracMT3300EXII).

[0051] The zeta potential (ZT) of the abrasive particles in the slurry (the overall ZT potential of the abrasive particles) is preferably within the following range. From the viewpoint of further increasing the grinding speed of the insulating material, the ZT potential of the abrasive particles is preferably +10 mV or higher, more preferably +20 mV or higher, even more preferably +25 mV or higher, particularly preferably +30 mV or higher, extremely preferably +40 mV or higher, and very preferably +50 mV or higher. There is no particular upper limit to the ZT potential of the abrasive particles; for example, it may be +200 mV or lower.

[0052] The zeta potential, or zeta potential, represents the surface potential of a particle. Zeta potential can be measured, for example, using a dynamic light scattering zeta potential measuring device (e.g., Beckman Coulter, Inc., trade name: Delsa Nano C). The zeta potential of a particle can be adjusted using additives. For example, by contacting a monocarboxylic acid (e.g., acetic acid) with particles containing cerium oxide, particles with a positive zeta potential can be obtained. Furthermore, by contacting ammonium dihydrogen phosphate, a carboxyl-containing material (e.g., polyacrylic acid), or the like with particles containing cerium oxide, particles with a negative zeta potential can be obtained.

[0053] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the cerium oxide content in the abrasive grains, based on the total abrasive grains (the total abrasive grains contained in the slurry), is preferably 50% by mass or more, more preferably more than 50% by mass, further preferably 60% by mass or more, particularly preferably 70% by mass or more, extremely preferably 75% by mass or more, very preferably 80% by mass or more, even more preferably 85% by mass or more, and even more preferably 90% by mass or more. The upper limit of the cerium oxide content in the abrasive grains, based on the total abrasive grains, can be 100% by mass. From the aforementioned viewpoint, the cerium oxide content in the abrasive grains, based on the total abrasive grains, can be 50 to 100% by mass.

[0054] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the cerium hydroxide content in the abrasive grains, based on the total abrasive grains (the total abrasive grains contained in the slurry), is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 9% by mass or more. The upper limit of the cerium hydroxide content in the abrasive grains, based on the total abrasive grains, can be 100% by mass. From the aforementioned viewpoint, the cerium hydroxide content in the abrasive grains, based on the total abrasive grains, can be 9 to 100% by mass. When the abrasive grains contain cerium oxide and cerium hydroxide, the upper limit of the cerium hydroxide content in the abrasive grains, based on the total abrasive grains, is preferably 50% by mass or less, more preferably less than 50% by mass, even more preferably 40% by mass or less, particularly preferably 30% by mass or less, extremely preferably 20% by mass or less, and very preferably 10% by mass or less.

[0055] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the cerium oxide content in the slurry, based on the total mass of the slurry, is preferably 0.005% by mass or more, more preferably 0.008% by mass or more, further preferably 0.01% by mass or more, particularly preferably 0.05% by mass or more, extremely preferably 0.08% by mass or more, very preferably 0.1% by mass or more, even more preferably 0.15% by mass or more, and even more preferably 0.18% by mass or more. From the viewpoint of improving the storage stability of the slurry, the upper limit of the cerium oxide content in the slurry, based on the total mass of the slurry, is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, extremely preferably 0.3% by mass or less, and very preferably 0.2% by mass or less. From the aforementioned viewpoint, the cerium oxide content in the slurry, based on the total mass of the slurry, is more preferably 0.005 to 5% by mass.

[0056] From the viewpoint of further improving the chemical interaction between the abrasive grains and the surface being ground, thereby further increasing the grinding speed of the insulating material, the lower limit of the cerium hydroxide content in the slurry, based on the total mass of the slurry, is preferably 0.005% by mass or more, more preferably 0.008% by mass or more, further preferably 0.01% by mass or more, particularly preferably 0.012% by mass or more, extremely preferably 0.015% by mass or more, and very preferably 0.018% by mass or more. From the viewpoint of easily avoiding abrasive grain aggregation, achieving better chemical interaction between the abrasive grains and the surface being ground, and easily and effectively utilizing the characteristics of the abrasive grains, the upper limit of the cerium hydroxide content in the slurry, based on the total mass of the slurry, is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and extremely preferably 0.2% by mass or less. From the aforementioned viewpoint, the cerium hydroxide content in the slurry, based on the total mass of the slurry, is more preferably 0.005 to 5% by mass. When the abrasive contains cerium oxide and cerium hydroxide, the upper limit of the cerium hydroxide content in the slurry is based on the total mass of the slurry, preferably 0.1% by mass or less, more preferably 0.05% by mass or less, even more preferably 0.03% by mass or less, and especially preferably 0.02% by mass or less.

[0057] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the abrasive content in the slurry, based on the total mass of the slurry, is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.1% by mass or more, particularly preferably 0.12% by mass or more, extremely preferably 0.14% by mass or more, very preferably 0.16% by mass or more, even more preferably 0.18% by mass or more, and even more preferably 0.2% by mass or more. From the viewpoint of improving the storage stability of the slurry, the upper limit of the abrasive content in the slurry, based on the total mass of the slurry, is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, and extremely preferably 0.3% by mass or less. From the aforementioned viewpoint, the abrasive content in the slurry, based on the total mass of the slurry, is more preferably 0.01 to 10% by mass.

[0058] Abrasive particles may contain particles including metal compounds containing metal M, or particles that do not contain metal M. Abrasive particles may also contain composite particles consisting of multiple particles in contact with each other. For example, abrasive particles may contain composite particles including a first particle and a second particle in contact with the first particle, or composite particles and free particles (e.g., a second particle that is not in contact with the first particle).

[0059] Regarding the abrasive grains of the slurry involved in this embodiment, from the viewpoint of further increasing the grinding speed of the insulating material, it is preferable to use a material comprising a first particle and a second particle in contact with the first particle, wherein the particle size of the second particle is smaller than that of the first particle, and the first particle contains cerium oxide and the second particle contains cerium compound. By using such abrasive grains, the grinding speed of the insulating material (e.g., silicon oxide) can be further increased. Reasons for such an increase in the grinding speed of the insulating material can be cited, for example, as follows. However, the reasons are not limited to those described below.

[0060] That is, the first particle, containing cerium oxide and having a larger particle size than the second particle, has a stronger mechanical effect (mechanical property) on the insulating material compared to the second particle. On the other hand, the second particle, containing cerium compound and having a smaller particle size than the first particle, has a weaker mechanical effect on the insulating material compared to the first particle, but has a stronger chemical effect (chemical property) on the insulating material due to its larger overall specific surface area (surface area per unit mass). Thus, by using both the first particle with strong mechanical effect and the second particle with strong chemical effect, a synergistic effect of increasing the grinding speed can be easily obtained.

[0061] Examples of cerium compounds that can be used as the second component include cerium hydroxides and cerium oxides. Compounds different from cerium oxides can be used as the second component. From the viewpoint of further improving the grinding speed of insulating materials, cerium compounds containing cerium hydroxides are preferred.

[0062] The particle size of the second particle is preferably smaller than that of the first particle. The size relationship between the first and second particles can be determined based on SEM images of the composite particles, etc. Generally, in particles with small particle sizes, the surface area per unit mass is larger compared to particles with large particle sizes, thus resulting in higher reactivity. On the other hand, the mechanical action (mechanical abrasive force) of small particles is smaller compared to particles with large particle sizes. However, in this embodiment, even when the particle size of the second particle is smaller than that of the first particle, the synergistic effect of the first and second particles can be observed, making it easy to balance excellent reactivity and mechanical action.

[0063] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the particle size of the first particle is preferably 15 nm or more, more preferably 25 nm or more, further preferably 35 nm or more, particularly preferably 40 nm or more, extremely preferably 50 nm or more, very preferably 80 nm or more, and even more preferably 100 nm or more. From the viewpoint of improving the dispersibility of abrasive particles and easily suppressing damage to the ground surface, the upper limit of the particle size of the first particle is preferably 1000 nm or less, more preferably 800 nm or less, further preferably 600 nm or less, particularly preferably 400 nm or less, extremely preferably 300 nm or less, very preferably 200 nm or less, and even more preferably 150 nm or less. From the aforementioned viewpoint, the particle size of the first particle is more preferably 15 to 1000 nm. The average particle size (average secondary particle size) of the first particle may also be within the above range.

[0064] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the particle size of the second particle is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more. From the viewpoint of improving the dispersibility of abrasive particles and easily suppressing damage to the ground surface, the upper limit of the particle size of the second particle is preferably 50 nm or less, more preferably 30 nm or less, even more preferably 25 nm or less, particularly preferably 20 nm or less, extremely preferably 15 nm or less, and very preferably 10 nm or less. From the aforementioned viewpoint, the particle size of the second particle is more preferably 1 to 50 nm. The average particle size (average secondary particle size) of the second particle may also be within the above range.

[0065] The first particle can have a negative zeta potential. The second particle can have a positive zeta potential.

[0066] Composite particles containing a first particle and a second particle can be obtained by the following methods: contacting the first particle with the second particle using a homogenizer, a high-pressure homogenizer, a ball mill, a bead mill, an ultrasonic processor, etc.; contacting the first particle with the second particle having opposite charges; and contacting the first particle with the second particle when the particle content is low.

[0067] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the cerium oxide content in the first particle is based on the total first particle (the total first particle contained in the slurry, hereinafter the same), preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. The first particle may also be substantially composed of cerium oxide (substantially 100% by mass of the first particle is cerium oxide).

[0068] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the cerium compound content in the second particle is based on the total amount of the second particle (the total amount of the second particle contained in the slurry, hereinafter the same), preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass or more. The second particle may also be substantially composed of cerium compound (in a manner in which 100% by mass of the second particle is substantially cerium compound).

[0069] The content of the second particle can be inferred by measuring the absorbance value obtained using a spectrophotometer with light of a specific wavelength through the slurry according to the following formula. That is, when a particle absorbs light of a specific wavelength, the transmittance of the region containing that particle decreases. Transmittance decreases not only due to particle absorption but also due to scattering, but the effect of scattering is small in the second particle. Therefore, in this embodiment, the content of the second particle can be inferred by measuring the absorbance value calculated using the following formula.

[0070] Absorbance = -LOG 10 (Light transmittance [%] / 100)

[0071] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the content of the first particle in the abrasive grains, based on the total abrasive grains (the total abrasive grains contained in the slurry, hereinafter the same), is preferably 50% by mass or more, more preferably more than 50% by mass, further preferably 60% by mass or more, particularly preferably 70% by mass or more, extremely preferably 75% by mass or more, very preferably 80% by mass or more, even more preferably 85% by mass or more, and even more preferably 90% by mass or more. From the viewpoint of further improving the grinding speed of insulating materials, the upper limit of the content of the first particle in the abrasive grains, based on the total abrasive grains, is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 91% by mass or less. From the aforementioned viewpoint, the content of the first particle in the abrasive grains, based on the total abrasive grains, is more preferably 50 to 95% by mass.

[0072] From the viewpoint of further improving the grinding speed of insulating materials, the lower limit of the content of the second particle in the abrasive grains, based on the total abrasive grains (the total abrasive grains contained in the slurry), is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 9% by mass or more. From the viewpoint of further improving the grinding speed of insulating materials, the upper limit of the content of the second particle in the abrasive grains, based on the total abrasive grains, is preferably 50% by mass or less, more preferably less than 50% by mass, even more preferably 40% by mass or less, particularly preferably 30% by mass or less, extremely preferably 20% by mass or less, and very preferably 10% by mass or less. From the aforementioned viewpoint, the content of the second particle in the abrasive grains, based on the total abrasive grains, is more preferably 5 to 50% by mass.

[0073] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the content of the first particle, based on the combined amount of the first particle and the second particle, is preferably 50% by mass or more, more preferably more than 50% by mass, further preferably 60% by mass or more, particularly preferably 70% by mass or more, extremely preferably 75% by mass or more, very preferably 80% by mass or more, even more preferably 85% by mass or more, and even more preferably 90% by mass or more. From the viewpoint of further improving the grinding speed of the insulating material, the upper limit of the content of the first particle, based on the combined amount of the first particle and the second particle, is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 91% by mass or less. From the aforementioned viewpoint, the content of the first particle, based on the combined amount of the first particle and the second particle, is more preferably 50 to 95% by mass.

[0074] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the content of the second particle, based on the combined amount of the first and second particles, is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 9% by mass or more. From the viewpoint of further improving the grinding speed of the insulating material, the upper limit of the content of the second particle, based on the combined amount of the first and second particles, is preferably 50% by mass or less, more preferably less than 50% by mass, even more preferably 40% by mass or less, particularly preferably 30% by mass or less, extremely preferably 20% by mass or less, and very preferably 10% by mass or less. From the aforementioned viewpoint, the content of the second particle, based on the combined amount of the first and second particles, is more preferably 5 to 50% by mass.

[0075] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the content of the first particle in the slurry, based on the total mass of the slurry, is preferably 0.005% by mass or more, more preferably 0.008% by mass or more, further preferably 0.01% by mass or more, particularly preferably 0.05% by mass or more, extremely preferably 0.08% by mass or more, very preferably 0.1% by mass or more, even more preferably 0.15% by mass or more, and even more preferably 0.18% by mass or more. From the viewpoint of improving the storage stability of the slurry, the upper limit of the content of the first particle in the slurry, based on the total mass of the slurry, is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, particularly preferably 0.5% by mass or less, extremely preferably 0.3% by mass or less, and very preferably 0.2% by mass or less. From the aforementioned viewpoint, the content of the first particle in the slurry, based on the total mass of the slurry, is more preferably 0.005 to 5% by mass.

[0076] From the viewpoint of further improving the chemical interaction between the abrasive grains and the surface being ground, thereby further increasing the grinding speed of the insulating material, the lower limit of the content of the second particle in the slurry, based on the total mass of the slurry, is preferably 0.005% by mass or more, more preferably 0.008% by mass or more, even more preferably 0.01% by mass or more, particularly preferably 0.012% by mass or more, extremely preferably 0.015% by mass or more, and very preferably 0.018% by mass or more. From the viewpoint of easily avoiding abrasive grain aggregation, achieving better chemical interaction between the abrasive grains and the surface being ground, and easily and effectively utilizing the characteristics of the abrasive grains, the upper limit of the content of the second particle in the slurry, based on the total mass of the slurry, is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, particularly preferably 0.5% by mass or less, extremely preferably 0.2% by mass or less, very preferably 0.1% by mass or less, even more preferably 0.05% by mass or less, even more preferably 0.03% by mass or less, and particularly preferably 0.02% by mass or less. In view of the above, the content of the second particle in the slurry is more preferably 0.005 to 5% by mass, based on the total mass of the slurry.

[0077] (Liquid medium)

[0078] There are no particular restrictions on the liquid medium, but deionized water, ultrapure water, or other similar water are preferred. The content of the liquid medium can be the remainder of the slurry excluding the content of other components, and there are no particular limitations.

[0079] (Any ingredients)

[0080] The slurry described in this embodiment may further contain any additives. Examples of such additives include materials having carboxyl groups (excluding compounds equivalent to polyoxyethylene compounds or water-soluble polymers), polyoxyethylene compounds, water-soluble polymers, oxidants (e.g., hydrogen peroxide), dispersants (e.g., phosphate-based inorganic salts), etc. Each additive can be used alone or in combination of two or more.

[0081] Examples of materials containing carboxyl groups include: monocarboxylic acids such as acetic acid, propionic acid, butyric acid, and valeric acid; hydroxy acids such as lactic acid, malic acid, and citric acid; dicarboxylic acids such as malonic acid, succinic acid, fumaric acid, and maleic acid; polycarboxylic acids such as polyacrylic acid and polymaleic acid; and amino acids such as arginine, histidine, and lysine.

[0082] Examples of polyoxyethylene compounds include polyalkylene glycols and polyoxyethylene derivatives.

[0083] Examples of polyalkylene glycols include polyethylene glycol, polypropylene glycol, and polybutanediol. Preferably, at least one polyalkylene glycol is selected from the group consisting of polyethylene glycol and polypropylene glycol, and more preferably polyethylene glycol.

[0084] Polyoxyalkylene derivatives are, for example, compounds in which functional groups or substituents are introduced into polyalkylene glycols, or compounds in which polyepoxides are added to organic compounds. Examples of such functional groups or substituents include alkyl ether groups, alkylphenyl ether groups, phenyl ether groups, styryl phenyl ether groups, glyceryl ether groups, alkylamine groups, fatty acid ester groups, and glycol ester groups. Examples of polyoxyethylene derivatives include polyoxyethylene alkyl ethers, polyoxyethylene bisphenol ethers (e.g., BA glycol series manufactured by Nippon Emulsifier Co., Ltd.), polyoxyethylene styrene phenyl ethers (e.g., Emulgen series manufactured by Kao Corporation), polyoxyethylene alkylphenyl ethers (e.g., Noigen EA series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.), polyoxyethylene polyglycerol ethers (e.g., SCE and SC-P series manufactured by Sakamoto Pharmaceutical Co., Ltd.), polyoxyethylene dehydrated sorbitol fatty acid esters (e.g., Sorgen TW series manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.), polyoxyethylene fatty acid esters (e.g., Emano series manufactured by Kao Corporation), polyoxyethylene alkylamines (e.g., Amiradine D manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.), and other compounds with addition to polyoxyalkylene oxides (e.g., Surfynol 465 manufactured by Nissin Chemical Co., Ltd., and TMP series manufactured by Nippon Emulsifier Co., Ltd.).

[0085] The term "water-soluble polymer" is defined as a polymer that dissolves in more than 0.1g of water per 100g of water. Polymers equivalent to the aforementioned polyoxyethylene compounds are not included in the category of "water-soluble polymers." There are no particular limitations on what constitutes a water-soluble polymer, but examples include: acrylic polymers such as polyacrylamide and polydimethylacrylamide; polysaccharides such as carboxymethyl cellulose, agar, curdlan, benzoin, cyclobenzoin, and pullulan; vinyl polymers such as polyvinyl alcohol, polyvinylpyrrolidone, and polyacrylaldehyde; glycerol polymers such as polyglycerol and polyglycerol derivatives; and polyethylene glycol, etc.

[0086] (Properties of the slurry)

[0087] From the viewpoint of improving the grinding speed of insulating materials, when the abrasive grains come into contact with the surface being ground (such as the surface being ground of the substrate) by contacting the slurry with the surface being ground, the slurry according to this embodiment provides a value of 0.13 or higher in X-ray photoelectron spectroscopy for the proportion of the smallest of the multiple valences of metal M. This valence proportion is the proportion of the valences of metal M in the abrasive grains (abrasive grains present on the surface being ground) that are in contact with the surface being ground. This valence proportion is the proportion when the total amount of metal M (all atoms) is set to 1, and is the proportion of the number of atoms having the desired valence (unit: at%). This valence proportion can be determined using the method described in the examples. The peak positions of X-ray photoelectron spectroscopy are caused by chemical shifts and vary depending on the valence. On the other hand, the number of atoms at each peak is proportional to the area of ​​the peak. Therefore, based on the shape of the spectrum, the ratio of the number of atoms of each valence can be obtained. Methods for adjusting the valence of metal M include oxidation treatment or reduction treatment of the abrasive grains. Examples of oxidation treatment methods include: treating abrasive grains with oxidizing agents; and high-temperature treatment in air or an oxygen atmosphere. Examples of reduction treatment methods include: treating abrasive grains with reducing agents; and high-temperature treatment in a reducing atmosphere such as hydrogen.

[0088] When abrasive grains are brought into contact with the surface being ground by bringing the slurry into contact with the surface being ground, the metal M can also have multiple valences. The smallest valence can be, for example, trivalent.

[0089] The surface to be polished may contain at least one element selected from the group consisting of silicon (Si), aluminum (Al), cobalt (Co), copper (Cu), gallium (Ga), germanium (Ge), arsenic (As), ruthenium (Ru), indium (In), tin (Sn), hafnium (Hf), thallium (Ta), tungsten (W), and platinum (Pt). The surface to be polished may also contain at least one element selected from the group consisting of metals, alloys, semiconductors, metal oxides, metal nitrides, metal carbides, metal phosphorus compounds, metal arsenic compounds, and organic compounds (e.g., polymers). The surface to be polished may contain an insulating material and may contain silicon oxide.

[0090] Examples of substrates having a polished surface include polished substrates. Examples of polished substrates include substrates on which the polishing material is formed on substrates related to semiconductor device manufacturing (e.g., semiconductor substrates with STI patterns, gate patterns, wiring patterns, etc.). Examples of polishing materials include insulating materials (such as silicon oxide) and metals. The polishing material can be a single material or multiple materials. When multiple materials are exposed on the polished surface, these can be considered as polishing materials. The polishing material can be a film (polished film), an insulating film (such as a silicon oxide film), a metal film, etc.

[0091] From the viewpoint of further improving the grinding speed of insulating materials, the ratio of the valence number after the abrasive grains come into contact with the surface being ground is preferably 0.14 or more, more preferably 0.15 or more, and even more preferably 0.16 or more. The ratio of the valence number may be 1 or less, or 0.8 or less.

[0092] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the pH of the slurry involved in this embodiment is preferably 2.0 or higher, more preferably 2.5 or higher, even more preferably 2.8 or higher, and particularly preferably 3.0 or higher. The lower limit of pH can be 3.2 or higher, 3.5 or higher, 4.0 or higher, 4.2 or higher, or 4.3 or higher. From the viewpoint of further improving the storage stability of the slurry, the upper limit of pH is preferably 7.0 or lower. The upper limit of pH can be 6.5 or lower, 6.0 or lower, 5.0 or lower, 4.8 or lower, 4.7 or lower, 4.6 or lower, 4.5 or lower, or 4.4 or lower. From the above viewpoint, pH is more preferably 2.0 to 7.0. The pH of the slurry is defined as the pH at a liquid temperature of 25°C.

[0093] The pH of the slurry can be adjusted using acidic components such as inorganic acids and organic acids, and alkaline components such as ammonia, sodium hydroxide, tetramethylammonium hydroxide (TMAH), imidazole, and alkanolamines. Buffers can also be added to stabilize the pH. Buffer solutions (liquids containing buffers) can also be prepared to add buffers. Examples of such buffer solutions include acetate buffers and phthalate buffers.

[0094] The pH of the slurry involved in this embodiment can be measured using a pH meter (e.g., model PHL-40 manufactured by DKK Corporation of East Asia). Specifically, after calibrating the pH meter at two points using phthalate pH buffer (pH: 4.01) and neutral phosphate pH buffer (pH: 6.86) as standard buffers, the pH meter electrode is placed in the slurry, and the value is measured after stabilization for more than 2 minutes. The temperature of both the standard buffer and the slurry is set to 25°C.

[0095] When using the slurry according to this embodiment as a CMP polishing slurry, the components of the polishing slurry can be formulated into a single-liquid polishing slurry for storage, or it can be formulated into a multi-liquid (e.g., two-liquid) polishing slurry group by mixing a slurry containing abrasive particles and a liquid medium (first liquid) with an additive liquid (second liquid) containing an additive and a liquid medium to form the polishing slurry, and then storing the components of the polishing slurry as a slurry and additive liquid group. The additive liquid may, for example, contain an oxidant. The components of the polishing slurry can also be formulated into polishing slurry groups of three or more liquids for storage.

[0096] In the aforementioned grinding slurry assembly, the slurry and additives are mixed to prepare the grinding slurry just before or during grinding. Furthermore, a single-component grinding slurry can be prepared as a storage solution for grinding slurry with a reduced liquid content and stored therein, and then diluted with a liquid medium for use during grinding. A multi-component grinding slurry assembly can be prepared as a slurry storage solution and an additive storage solution with a reduced liquid content and stored therein, and then diluted with a liquid medium for use during grinding.

[0097] <Screening Methods for Pulp>

[0098] The slurry selection method according to this embodiment includes: a contact step, in which the abrasive particles are brought into contact with the surface to be ground (such as the surface to be ground of a substrate) by contacting the slurry containing abrasive particles and a liquid medium; and a measurement step, in which the valence of the metal contained in the abrasive particles is determined by X-ray photoelectron spectroscopy while the abrasive particles are in contact with the surface to be ground, wherein the abrasive particles contain at least one metal compound selected from the group consisting of metal oxides and metal hydroxides, and the metal compound contains metals that may have multiple valences, and in the measurement step, the proportion of the smallest valence among the multiple valences of the metal is obtained. In the slurry selection method according to this embodiment, a slurry that can improve the grinding speed of insulating materials can be selected.

[0099] In the contact process, for example, the slurry can be brought into contact with the surface to be ground by immersing the substrate having the surface to be ground in the slurry. The surface to be ground can also be dried between the contact process and the measurement process.

[0100] The measurement process can be performed after the contact process. X-ray photoelectron spectroscopy in the measurement process can be performed using the methods described in the examples.

[0101] The slurry screening method described in this embodiment may also include a determination step after the measurement step, which determines the proportion of the valence obtained in the measurement step. In the determination step, for example, a slurry with a valence proportion of 0.13 or higher is selected.

[0102] <Grinding Method>

[0103] The grinding method (such as a matrix grinding method) according to this embodiment includes a grinding process in which a slurry with a value of 0.13 or higher, obtained in the determination step of the slurry screening method according to this embodiment, is used to grind the surface to be ground (such as the surface to be ground of a matrix).

[0104] In the grinding process, for example, while the material to be ground, having a substrate, is pressed onto a grinding pad (grinding cloth) on a grinding platform, the slurry is supplied between the material to be ground and the grinding pad, causing the substrate and the grinding platform to move relative to each other, thereby grinding the surface of the material to be ground. In the grinding process, at least a portion of the material to be ground is removed, for example, through grinding. By using the slurry to grind the material to be ground (e.g., an insulating material such as silicon oxide) formed on such a substrate, excess material is removed, thereby eliminating unevenness on the surface of the material to be ground, resulting in a smooth surface overall.

[0105] In the polishing method according to this embodiment, a conventional polishing apparatus can be used as the polishing device, which includes a holder for holding a substrate having the surface to be polished and a polishing platform for attaching a polishing pad. A motor with adjustable rotation speed is installed on both the holder and the polishing platform. Examples of polishing devices that can be used include the F-REX300 polishing device manufactured by Ebara Manufacturing Co., Ltd., or the MIRRA polishing device manufactured by Applied Materiels Co., Ltd.

[0106] As a polishing pad, common nonwoven fabrics, foams, and non-foamed materials can be used. As a material for the polishing pad, resins such as polyurethane, acrylic resin, polyester, acrylate copolymer, polytetrafluoroethylene, polypropylene, polyethylene, poly4-methylpentene, cellulose, cellulose ester, polyamide (e.g., nylon and aromatic polyamides), polyimide, polyimide amide, polysiloxane copolymer, ethylene oxide compounds, phenolic resin, polystyrene, polycarbonate, and epoxy resin can be used. As a material for the polishing pad, especially from the viewpoint of superior polishing speed and flatness, at least one material from the group consisting of foamed polyurethane and non-foamed polyurethane is preferred. It is preferable to perform a groove processing on the polishing pad to allow for slurry accumulation.

[0107] There are no restrictions on the grinding conditions; however, to prevent the substrate from flying out, the upper limit of the rotation speed of the grinding platform is preferably 200 min. -1 (min -1 From the viewpoint of easily suppressing grinding damage, the upper limit of the grinding pressure (processing load) applied to the substrate is preferably 100 kPa or less. It is preferable to continuously supply the slurry to the grinding pad using a pump or the like during grinding. There is no limitation on the supply amount, but it is preferable that the surface of the grinding pad is always covered with slurry.

[0108] This embodiment is preferably used for polishing a surface containing silicon oxide. According to this embodiment, it is possible to provide an application of a slurry in polishing a surface containing silicon oxide. This embodiment can be suitably used in the formation of STI and the high-speed polishing of interlayer insulating materials. The lower limit of the polishing speed for the insulating material (e.g., silicon oxide) is preferably 70 nm / min or more, more preferably 100 nm / min or more, further preferably 150 nm / min or more, particularly preferably 180 nm / min or more, and extremely preferably 200 nm / min or more.

[0109] This embodiment can also be used in the grinding of pre-metal insulating materials. Examples of pre-metal insulating materials include silicon oxide, phospho-silicate glass, borosilicate-phospho-silicate glass, silicon oxyfluoride, and fluorinated amorphous carbon.

[0110] This embodiment can also be applied to materials other than insulating materials such as silicon oxide. Examples of such materials include: high dielectric constant materials such as Hf-based, Ti-based, and Ta-based oxides; semiconductor materials such as silicon, amorphous silicon, SiC, SiGe, Ge, GaN, GaP, GaAs, and organic semiconductors; phase change materials such as GeSbTe; inorganic conductive materials such as ITO; and polymer resin materials such as polyimide-based, polybenzoxazole-based, acrylic-based, epoxy-based, and phenolic-based polymers and resins.

[0111] This embodiment can be applied not only to film-like grinding objects, but also to various substrates made of glass, silicon, SiC, SiGe, Ge, GaN, GaP, GaAs, sapphire, plastics, etc.

[0112] This embodiment can be used not only in the manufacture of semiconductor components, but also in the manufacture of image display devices such as TFTs and organic ELs; optical components such as photomasks, lenses, prisms, optical fibers, and single-crystal scintillators; optical components such as optical switching elements and optical waveguides; light-emitting elements such as solid-state lasers and blue laser LEDs; and magnetic storage devices such as disks and magnetic heads.

[0113] Example

[0114] The present invention will now be described in detail based on the embodiments, but the present invention is not limited to the following embodiments.

[0115] <Preparation of Cerium Oxide Slurry>

[0116] A cerium oxide slurry (pH: 7) containing cerium oxide particles (the first particle, hereinafter referred to as "cerium oxide particles") was prepared by mixing cerium oxide particles with ammonium dihydrogen phosphate (molecular weight: 97.99), a product manufactured by Wako Pure Chemical Industries, Ltd. The amount of ammonium dihydrogen phosphate was adjusted to 1% by mass based on the total amount of cerium oxide particles.

[0117] An appropriate amount of cerium oxide slurry was added to Microtrac MT3300EXII (manufactured by Microtrac BEL Co., Ltd.), and the average particle size of the cerium oxide particles was measured. The displayed average particle size value was taken as the average particle size (average secondary particle size). The average particle size of the cerium oxide particles in the cerium oxide slurry was 145 nm.

[0118] A suitable amount of cerium oxide slurry was added to a product manufactured by Beckman Coulter, Inc. under the trade name DelsaNano C, and two measurements were performed at 25°C. The average value of the displayed zeta potential was obtained as the zeta potential. The zeta potential of the cerium oxide particles in the cerium oxide slurry was -55 mV.

[0119] <Preparation of Cerium Hydroxide Slurry>

[0120] (Synthesis of cerium hydroxide)

[0121] A solution was obtained by mixing 480 g of a 50% (w / w) aqueous solution of Ce(NH4)2(NO3)6 (manufactured by Nippon Kagaku Kogyo Co., Ltd., trade name: CAN50 solution) with 7450 g of pure water. Then, while stirring the solution, 750 g of an imidazole aqueous solution (10% (w / w), 1.47 mol / L) was added dropwise at a mixing rate of 5 mL / min to obtain a precipitate containing cerium hydroxide. The mixture was then stirred at 20 °C for 500 min. -1 The synthesis of cerium hydroxide was carried out using a three-vane pitch paddle with a total blade length of 5 cm.

[0122] The obtained precipitate (containing cerium hydroxide) was centrifuged (4000 min). -1 After 5 minutes, the liquid phase was removed by decantation, thus performing solid-liquid separation. 10g of the particles obtained by solid-liquid separation was mixed with 990g of water, and the particles were dispersed in water using an ultrasonic cleaner to prepare a cerium hydroxide slurry containing particles containing cerium hydroxide (the second particle, hereinafter referred to as "cerium hydroxide particles") (particle content: 1.0% by mass).

[0123] (Determination of average particle size)

[0124] The average particle size (mean secondary particle size) of cerium hydroxide particles in a cerium hydroxide slurry was determined using a Beckman Coulter N5 instrument, and the result was 10 nm. The determination method is as follows: First, approximately 1 mL of the test sample (cerium hydroxide slurry, aqueous dispersion) containing 1.0% by mass of cerium hydroxide particles was placed in a 1 cm square tank, and then the tank was placed inside the N5 instrument. The refractive index of the test sample information in the N5 instrument was set to 1.333, the viscosity was set to 0.887 mPa·s, and the measurement was performed at 25°C. The displayed value was recorded as the unimodal size mean.

[0125] (Measurement of zeta potential)

[0126] A suitable amount of cerium hydroxide slurry was added to a product manufactured by Beckman Coulter, Inc. under the trade name DelsaNano C, and two measurements were performed at 25°C. The average value of the displayed zeta potential was obtained as the zeta potential. The zeta potential of the cerium hydroxide particles in the cerium hydroxide slurry was +50 mV.

[0127] (Structural analysis of cerium hydroxide particles)

[0128] A suitable amount of cerium hydroxide slurry was vacuum dried to separate the cerium hydroxide particles, and then thoroughly washed with pure water to obtain a sample. The obtained sample was analyzed using FT-IR ATR. The results showed that, in addition to observing the presence of hydroxide ions (OH-),... - In addition to the peak of ), peaks based on nitrate ions (NO3) were also observed. - The peak of NH4+ was observed. Furthermore, for the same sample, XPS (N-XPS) measurements of nitrogen were performed, and no peaks based on NH4+ were observed. + The peaks observed were based on nitrate ions. Based on these results, it can be confirmed that cerium hydroxide particles contain at least a portion of particles with nitrate ions bonded to cerium. Furthermore, since at least a portion of the cerium hydroxide particles contain particles with hydroxide ions bonded to cerium, it can be confirmed that the cerium hydroxide particles contain cerium hydroxide. Based on these results, it can be confirmed that cerium hydroxide contains hydroxide ions bonded to cerium.

[0129] <Preparation of CMP Slurry>

[0130] (Example 1)

[0131] Using a two-bladed agitator, the cerium hydroxide slurry was mixed with deionized water at a stirring speed of 300 rpm to obtain a mixture. Then, while stirring the mixture, the cerium oxide slurry was mixed with the mixture, and then stirred while being irradiated with ultrasound using an ultrasonic cleaner (device name: US-105) manufactured by SND Corporation. Thus, a CMP slurry containing composite particles comprising cerium oxide particles and cerium hydroxide particles in contact with the cerium oxide particles was prepared. The abrasive content (total) in the CMP slurry was 0.2% by mass, and the mass ratio of cerium oxide particles to cerium hydroxide particles was 10:1 (oxide:hydride).

[0132] (Example 2)

[0133] Using a two-bladed agitator, 400g of the cerium hydroxide slurry was mixed with 1600g of deionized water while stirring at 300rpm. The mixture was then stirred while being irradiated with ultrasound using an ultrasonic cleaner (US-105) manufactured by SND Corporation. This resulted in the preparation of a CMP slurry containing cerium hydroxide particles (cerium hydroxide particle content: 0.2% by mass).

[0134] (Example 3)

[0135] Cerium dioxide particles (cerium oxide particles A, different from those in Example 1) were prepared as abrasives. A CMP slurry (abrasive content: 0.2% by mass) was prepared by mixing the cerium dioxide particles with ion-exchanged water.

[0136] (Example 4)

[0137] Cerium dioxide particles (cerium oxide particles B, different from those in Example 1 and cerium oxide particles A) were prepared as abrasives. A CMP slurry (abrasive content: 0.2% by mass) was prepared by mixing the cerium dioxide particles with ion-exchanged water.

[0138] (Comparative Example 1)

[0139] Cerium dioxide particles (cerium oxide particles C, which are different from the cerium oxide particles and cerium oxide particles A and B in Example 1) were prepared as abrasives. A CMP slurry (abrasive content: 0.2% by mass) was prepared by mixing the cerium dioxide particles with ion-exchanged water.

[0140] (Comparative Example 2)

[0141] After drying the cerium hydroxide slurry, the cerium hydroxide particles were kept at 180°C for 24 hours. Then, the cerium hydroxide particles were mixed with deionized water. Thus, a CMP slurry containing cerium hydroxide particles as abrasives was prepared (abrasive content: 0.2% by mass).

[0142] <Determination of Valence>

[0143] A centrifuge (trade name: OptimaMAX-TL) manufactured by Beckman Coulter, Inc. was used at a centrifugal acceleration of 1.1 × 10⁻⁶. 4 G treated the CMP slurry (abrasive content: 0.2% by mass) for 30 minutes, thereby separating the solid and liquid phases (supernatant). After removing the liquid phase, the solid phase was vacuum dried at 25°C for 24 hours to obtain the test sample. The valence A of cerium in the abrasive particles of the test sample was determined by X-ray photoelectron spectrophotometry.

[0144] Next, as an unpatterned blanket wafer, a substrate to be polished was prepared having a 2 μm thick silicon oxide film (SiO2 film) formed on a silicon substrate using plasma CVD. The substrate to be polished was immersed in CMP slurry (abrasive content: 0.2% by mass) for 1 minute. After being removed from the CMP slurry, the substrate was dried using a nitrogen gun. Furthermore, the valence B of cerium contained in the abrasive grains present on the polished surface of the substrate was determined using X-ray photoelectron spectroscopy.

[0145] The X-ray photoelectron spectrometry (XPS) apparatus used was the Thermo Fisher Scientific instrument, trade name "K-Alpha". The measurement conditions are as follows.

[0146] [XPS Requirements]

[0147] Energy: 100eV

[0148] Total number of times: 10

[0149] Binding energy: 870–930 eV range

[0150] Excitation X-rays: Monochromatic Al Kα1,2 rays (1486.6 eV)

[0151] X-ray diameter: 200 μm

[0152] Photoelectron extraction angle: 45°

[0153] Next, regarding the valence A and valence B of cerium, the waveforms originating from the trivalent and tetravalent valences were separated using the analysis software provided with the apparatus. Waveform separation was performed according to the method described in the literature "Surface Science" (Vol. 563 (2004) pp. 74-82). Furthermore, the proportion of the trivalent valence was calculated based on the following formula. The measurement results are shown in Table 1.

[0154] The proportion of trivalents = (amount of trivalents [at%]) / (amount of trivalents [at%] + amount of tetravalents [at%])

[0155] <pH Measurement>

[0156] The pH of the CMP slurry was determined using a PHL-40 slurry manufactured by DKK Corporation of East Asia. The results are shown in Table 1.

[0157] <Measurement of ζ potential>

[0158] An appropriate amount of CMP slurry was added to "DelsaNano C" manufactured by Beckman Coulter, Inc. Two measurements were performed at 25°C, and the average of the displayed zeta potentials was used. The results are shown in Table 1.

[0159] <Determination of the average particle size of abrasive grains>

[0160] The average particle size of the abrasive particles was measured by adding appropriate amounts of each of the CMP slurries of Examples 1 and 4 (abrasive content: 0.2% by mass) to Microtrac MT3300EXII manufactured by Microtrac BEL Co., Ltd. Furthermore, the average particle size of the abrasive particles was measured by adding appropriate amounts of each of the CMP slurries of Examples 2, 3, Comparative Examples 1 and 2 (abrasive content: 0.2% by mass) to N5 manufactured by Beckman Coulter Co., Ltd. The average particle size value obtained was taken as the average particle size (average secondary particle size). The measurement results are shown in Table 1.

[0161] <Determination of Grinding Speed>

[0162] The substrates used in the evaluation of the above valences were polished using the above-mentioned CMP slurries (abrasive content: 0.2% by mass) under the following polishing conditions.

[0163] [CMP grinding conditions]

[0164] Grinding equipment: MIRRA (manufactured by Applied Materials)

[0165] CMP slurry flow rate: 200 mL / min

[0166] Abrasive pad: Foamed polyurethane resin with independent air bubbles (manufactured by Dow Chemical Co., Ltd., Japan, model IC1010)

[0167] Grinding pressure: 13 kPa (2.0 psi)

[0168] Rotation speed of the substrate being polished and the polishing platform: Substrate being polished / Polishing platform = 93 / 87 rpm

[0169] Grinding time: 1 min

[0170] Wafer cleaning: After CMP treatment, the wafer is cleaned with water while being subjected to ultrasonic waves, and then dried by a rotary dryer.

[0171] The grinding rate (SiO2RR) of the silicon oxide film after grinding and cleaning under the stated conditions was determined by the following formula. The measurement results are shown in Table 1. The difference in film thickness between the silicon oxide film before and after grinding was determined using an optical interferometric film thickness measuring device (manufactured by Filmetrics Inc., trade name: F80).

[0172] Grinding speed (RR) = (Difference in silicon oxide film thickness before and after grinding [nm]) / (Grinding time: 1 [min])

[0173] [Table 1]

[0174]

Claims

1. A slurry containing abrasive particles and a liquid medium, wherein, The abrasive grains contain metal hydroxides. The metal hydroxide comprises a metal having multiple valences. When the abrasive grains are brought into contact with the surface being ground by contacting the slurry, the slurry gives a value of 0.13 or higher in X-ray photoelectron spectroscopy for the proportion of the smallest of the plurality of valences of the metal. The valence ratio refers to the proportion of valences present in the metal of the abrasive grains on the surface being ground, specifically the proportion of atoms with the target valence when all atoms of the metal are set to 1. The abrasive grains comprise a first particle and a second particle in contact with the first particle. The particle size of the second particle is smaller than that of the first particle. The first particle contains cerium oxide. The second particle contains cerium hydroxide.

2. The slurry according to claim 1, wherein, The average particle size of the first particle is greater than 40 nm.

3. The slurry according to claim 1, wherein, The average particle size of the first particle is less than 400 nm.

4. The slurry according to claim 1, wherein, The average particle size of the second particle is greater than 3 nm.

5. The slurry according to claim 1, wherein, The average particle size of the second particle is less than 15 nm.

6. The slurry according to claim 1, wherein, The first particle has a negative zeta potential, and the second particle has a positive zeta potential.

7. The slurry according to claim 1, wherein, Based on the total mass of the slurry, the content of cerium oxide is 0.1% by mass or more.

8. The slurry according to claim 1, wherein, Based on the total mass of the slurry, the content of cerium oxide is less than 0.3% by mass.

9. The slurry according to claim 1, wherein, Based on the total mass of the slurry, the content of the cerium hydroxide is 0.01% by mass or more.

10. The slurry according to claim 1, wherein, Based on the total mass of the slurry, the content of the cerium hydroxide is less than 0.03% by mass.

11. The slurry according to claim 1, wherein, Based on the total mass of the slurry, the content of the abrasive particles is 0.1% by mass or more.

12. The slurry according to claim 1, wherein, Based on the total mass of the slurry, the content of the abrasive particles is less than 1% by mass.

13. The slurry according to claim 1, wherein, pH ranges from 2.0 to 7.

0.

14. The slurry according to claim 1, wherein, pH is above 3.

0.

15. The slurry according to claim 1, wherein, pH below 4.

5.

16. The slurry according to claim 1, wherein, The surface to be ground comprises at least one selected from the group consisting of silicon, aluminum, cobalt, copper, gallium, germanium, arsenic, ruthenium, indium, tin, hafnium, thallium, tungsten, and platinum.

17. The slurry according to claim 1, wherein, The surface being ground contains silicon oxide.

18. The slurry according to claim 1, wherein, The zeta potential of the abrasive particles in the slurry is above +10mV.

19. The slurry according to claim 1, wherein, The zeta potential of the abrasive particles in the slurry is above +40mV.

20. The slurry according to claim 1, wherein, The zeta potential of the abrasive particles in the slurry is below +200mV.

21. A multi-liquid grinding slurry assembly, wherein, The method is to mix the slurry according to any one of claims 1 to 20 with an additive liquid containing additives and a liquid medium to form a grinding slurry, wherein the components of the grinding slurry are divided into the slurry and the additive liquid.

22. A grinding method comprising the step of grinding a surface using a slurry. The slurry is a slurry with a value of 0.13 or higher, obtained in the determination step of the valence method of the slurry screening process. The screening method for the slurry includes: The process of bringing the abrasive particles into contact with the surface being ground by bringing a slurry containing abrasive particles and a liquid medium into contact with the surface being ground; as well as In the measurement process, with the abrasive grains in contact with the surface being ground, the valence of the metals contained in the abrasive grains is determined using X-ray photoelectron spectrometry. The abrasive grains contain metal hydroxides. The metal hydroxide comprises a metal having multiple valences. The abrasive grains comprise a first particle and a second particle in contact with the first particle. The particle size of the second particle is smaller than that of the first particle. The first particle contains cerium oxide. The second particle contains cerium hydroxide. In the determination process, the proportion of the smallest valence among the plurality of valences of the metal is obtained. The valence ratio is the ratio of the valences present in the metal of the abrasive grains on the surface being ground, and the ratio of the number of atoms with the target valence when all atoms of the metal are set to 1.

23. The grinding method according to claim 22, wherein, The minimum valence is trivalent.

24. The grinding method according to claim 22, wherein, The metal includes cerium.

25. The grinding method according to claim 22, wherein, The average particle size of the abrasive grains is above 100 nm.

26. The grinding method according to claim 22, wherein, The average particle size of the abrasive grains is below 300 nm.

27. The grinding method according to claim 22, wherein, Based on the total mass of the slurry, the content of the abrasive particles is 0.1% by mass or more.

28. The grinding method according to claim 22, wherein, Based on the total mass of the slurry, the content of the abrasive particles is less than 1% by mass.

29. The grinding method according to claim 22, wherein, The pH of the slurry is above 3.

0.

30. The grinding method according to claim 22, wherein, The pH of the slurry is below 4.

5.

31. The grinding method according to claim 22, wherein, The surface being ground contains silicon oxide.

32. The grinding method according to any one of claims 22 to 31, wherein, The proportion of the smallest valence among the plurality of valences of the metal is 0.8 or less.

Citation Information

Patent Citations

  • Polishing method

    JP1996022970A

  • Cerium oxide abrasive agent and polishing method of substrate

    JP1998106994A

  • Polishing agent, concentrated one-pack type polishing agent, two-pack type polishing agent and method for polishing sustrate

    CN102473622A

  • Cmp polishing liquid, and polishing method

    CN106471090A

  • Cerium Oxide Abrasive, Method for Producing Cerium Oxide Abrasive, and Polishing Method

    US20160272860A1